Surgical Repair of a Sinus of Valsalva Aneurysm: A 22-Year Single-Center Experience - Lee, Jun Ho; Yang, Ji-Hyuk; Park, Pyo Won; Song, Jinyoung; Huh, June; Kang, I-Seok; Jun, Tae-Gook (The Thoracic and Cardiovascular Surgeon, 2019)
Background Several reports described the repair of sinus of Valsalva aneurysms (SVAs); however, there is still debate regarding the optimal method of operation. We investigated the determinants of the development of significant aortic regurgitation (AR) and long-term survival after surgical repair.Methods Between January 1995 and December 2016, 71 patients (31 females; median age: 33.3 years) underwent surgical SVA repair with (n = 60) or without (n = 11) rupture. Aortic valvuloplasty (AVP) was performed using Trusler's technique in 28 patients (39.4%), and 11 patients (15.5%) underwent aortic valve replacement during the first operation.Results There was no early mortality, and three deaths occurred during follow-up (median: 65.4 months). Patients with grade II preoperative AR who underwent AVP tended to develop significant postoperative AR, but freedom from significant AR did not differ statistically (p = 0.387). Among patients who underwent AVP, freedom from significant AR did not differ statistically between those with grades I and II and those with grades III and IV (p = 0.460).Conclusion Surgical repair of SVA with or without rupture can be performed safely using the dual approach technique. Concomitant aortic valve repair can be performed without difficulty and should be recommended not only for patients with moderate or severe preoperative AR (grades III and IV) but also for those with minimal or mild preoperative AR (grades I and II), whose aortic valve geometry needs correction.
Keywords: aortic regurgitation; aneurysm; aorta/aortic